Prenamemba zdravilnih učinkovin (»drug repurposing«) za terapijo raka - Pečnik, Matija (Placebo, 2023)
High prevalence of cancer in developed countries makes it the second leading cause of death. The shortage and barriers of the development of new anticancer drugs are leading to a search for anticancer effects in existing drugs through a strategy of drug repurposing. This strategy is cost-effective and crucial for the acceleration of active substances to clinical trials. The success of drug repurposing is greater because of significant advances of in silico methods, genomics and proteomics.
Keywords: klinična preizkušanja; molekulsko sidranje; prenamemba zdravilnih učinkovin; Rak (medicina); rakava obolenja; rešetanje visoke zmogljivosti; terapija raka; Zdravilne učinkovine; Zdravljenje